Foregut Cystic Malformations in the Pancreas. Are Definitions Clearly Established? - Gómez Mateo, María del Carmen; Muñoz Forner, Elena; Sabater Ortí, Luis; Ferrández Izquierdo, Antonio (JOP. Journal of the Pancreas, 2011)
Context Foregut cystic malformations are common lesions in the mediastinum but are rarely found in subdiaphragmatic locations. Only a few cases have been described within the pancreas where they can easily be misdiagnosed as cystic neoplasms. Case report We herein present the case of a 37-year-old female with acute cholangitis in whom a diagnostic work-up revealed a 1 cm solid-cystic heterogeneous lesion located at the head of the pancreas. The patient underwent a pancreaticoduodenectomy. Pathological evaluation demonstrated a cystic cavity lined by pseudostratified tall columnar ciliated epithelium with goblet cells, but lacking cartilage or smooth muscle bundles. Thus, the final diagnosis of the lesion was a ciliated foregut cyst of the pancreas. Conclusions A review of the cases published regarding these lesions shows great variability in the taxonomy and a lack of accuracy in the definitions of each different subtype. An easy to use algorithm for the diagnosis of foregut cystic malformations subtypes, based on epithelial lining and wall features, is presented. Image: Diagnostic algorithm of the different foregut cystic malformations.